Verbal Bullying and Mental Health in Elementary School Students - Shofi Luthfiani, Isnania; Abduh, Muhammad (Journal of World Science, 2024)
Bullying is a dangerous problem in education today, especially for students. Most students are victims of bullying from their schoolmates. Bullying in students that is carried out continuously will have an impact on mental health. Many victims of bullying have not received an education, so they do not dare to reveal it to teachers or parents. This condition makes it difficult for teachers to monitor and follow up on bullying cases at school. This study aims to determine what causes children to be bullied and the impact of bullying behaviour on fourth-grade students of SD Muhammadiyah 1 Sragen. This research uses a qualitative case study type. Data collection techniques used observation, questionnaires, interviews, and documentation. Primary data sources were obtained from observations and interviews with students, teachers and parents. The secondary data sources are through records and journals. Based on the results of research at SD Muhammadiyah 1 Sragen, the results show that the form of bullying behaviour is direct verbal, physical, and psychological bullying. The factors that cause this case are influenced by parenting style, play environment, socialization and mass media. So that this treatment has an impact on the behaviour of victims who are traumatized, become quiet, not confident, and have feelings of fear. This fourth-grade student showed that it was too severe, for example, cursing with parents' nicknames, slapping hands on the head, and fighting with friends. Efforts made by parents and teachers to increase children's supervision of relationships are through the parent-teacher meeting evaluation program.